School Learning Environment Indicies - Nordin Abu Bakar, Kamaruddin Kamarulzaman, Kamis Hariri, Jusoh Osman, Ismail Ramlee, (Universiti Pendidikan Sultan Idris, 2008)
School Learning Environment Indicies by Nordin Abu Bakar, Kamaruddin Kamarulzaman, Kamis Hariri, Jusoh Osman, Ismail Ramlee,